Estimation of gas void formation in statically cooled waxy crude oil using online capacitance measurement. (October 2015) - Shafquet, Areeba; Ismail, Idris; Japper-Jaafar, Azuraien; Sulaiman, Shaharin A.; Chala, Girma T.
Highlights: The distance between the ECT sensors is an optimum calculated distance. An ECT sensor calibration was performed with air (low) and crude oil at 80 °C (high). Due to thermal shrinkage, the gas voids formed in a statically cooled waxy crude oil. Velocity of the crude oil was calculated at 75 °C during the standardization of flow loop. Location & volume of gas voids rely strongly on cooling and flow rates in the pipe. Abstract: Waxy crude oil is one of the massively produced petroleum reserves in the oil and gas industry. It possesses two different natures at different conditions. At a temperature above its wax appearance temperature it functions as a Newtonian fluid. Moreover, when it flows in a subsea environment where the temperature drops, the occurrence of non-Newtonian fluid would appear. However, it is mandatory to prevent the pipelines from building up with the solid wax layer, or else a strong paraffinic gel structure would plug the flow of the waxy crude oil. This gel accumulation results in the emergence of thermal shrinkage where gas voids consequently occur. A Malay Basin waxy crude oil has used for this study to investigate the gas void formation in statically cooled waxy crude oil using an online Electrical Capacitance Tomography (ECT) measurement. This paper has been focused on the development of a non-invasive, non-intrusive approach for the visualization of waxy crude oil by applying the ECT system. The online inspection of the behavior of waxy crude oil is important so that the appropriate action can be taken during the gas void formation within a gelled crude oil. An experimental study was conducted on a 1.18 in. circular flow loop rig at distinct temperatures to assess the behavior and formation of gas voids formed due to thermal shrinkage. A capacitance sensor with dual planes consisting of eight electrodes per plane was installed on the rig to capture the images and measure the raw capacitance. Gas voids within a range of 8–14% were observed within the gelled crude oil based on different cooling temperatures. It has been found from the analysis that the gas voids follow an increasing trend with a decrease in temperature and cooling rate.